BIOTECNOLOGIA, BIODIVERSIDADE E DESENVOLVIMENTO LOCAL: REGULAMENTAÇÃO E DEMANDAS TÉCNICAS E TECNOLÓGICAS - Hasenclever, Lia; Klein, Helena Espellet; Santos, Luan (Acta Scientiae et Technicae; v. 1 n. 1 (2013): I Simpósio de Biotecnologia e Biodiversidade, 2013)
The paper presents a brief overview of the sector of medicinal plants and phytomedicines, and analyzes whether the current regulation of research and development activities and appropriability of knowledge associated with the sector, as well as the technical and technology demands constitute a hindrance or not to the proposed policies for the development of this sector in Brazil. The methodology includes a bibliographical research and consultation with fi rms and experts on the subject. We conclude that although the sector has enormous potential for local development, both regulatory and technical and technological bottlenecks identifi ed are great diffi culties in the operationalization of this potential.